Sosialisasi Stunting dan Pencegahan Stunting Era New Normal di Kelurahan Tampan Kota Pekanbaru - Utama, Fajar Fadilla; Kurniawan, Ridho; Tendryabeng, Tendryabeng; Apriyani, Etty; Alfito, Muhammad Rida; Andrianti, Desi; Najah, Malihatun; Maharani, Raja Silvia; Fadilla, Elfina Septiani; Istiani, Rizky Mulya (MASPUL JOURNAL OF COMMUNITY EMPOWERMENT, 2022)
Stunting is a chronic malnutrition problem caused by inadequate nutritional intake for a long time due to feeding that is not in accordance with nutritional needs. The purpose of this activity is to add insight to parents in choosing nutritious foods to avoid stunting. The existence of stunting prevention socialization can help the community to change their lifestyle for the better. The implementation of this Stunting Prevention program is carried out using a participatory approach, meaning that the fostered partners will be actively involved in every stage and coaching activities carried out through introduction and education about stunting, behavior education clean and healthy living, followed by the provision of additional food for toddlers, pregnant women, and children affected by stunting. Some of the steps we take in preventing stunting in the Tampan Village are: 1. Survey and data search, 2. Socialization and education on stunting, 3. Education on clean and healthy living behavior, 4. Provision of additional food. Stunting is a dangerous disease condition and must be continuously considered by the community and the government. If it is not continued, it is feared that Indonesia will experience a Lost Generation crisis. The Kukerta Team of the University of Riau took the initiative and intensified this stunting prevention program, as a form of concern for the future of the Indonesian nation. There are several programs and stages that have been implemented. Such as education and outreach about stunting and how to prevent it, education about health and hygiene, and providing additional food.